Modulating autophagy in KRAS mutant colorectal cancer using combination of oncolytic reovirus and carbamazepine. - Aaron Shaykevich; Danbee Chae; Isaac Silverman; Sanjay Goel; Radhashree Maitra (PLoS ONE)
Oncolytic reovirus is a potential therapeutic for colorectal cancer patients with a mutant KRAS gene. Reovirus hijacks the autophagic machinery and preferentially induces apoptosis in patients with a KRAS mutation. However, reovirus on its own is not currently a viable treatment and requires enhancement with combination therapies. Carbamazepine, an FDA-approved drug in use for epilepsy, is an autophagy inducer and is used in this study in conjunction with reovirus. The dual treatment was able to reduce cancer viability in mutated KRAS cell lines and was more effective than with reovirus alone. Carbamazepine and reovirus increased autophagy-related proteins and mRNA in mutant KRAS compared to wildtype KRAS which is crucial for autophagy-induced apoptosis. Transmission electron microscopy results show increased autophagosome formation in the combination therapy, as well as a decrease in condensed chromatin. The combination therapy effectively increased the apoptosis induced by reovirus alone and is a viable treatment for patients with a mutant KRAS.